6747 Shares

Can someone help me with this algebra 2 question? Topic: Parenthesis signs
June 25, 2019 / By Lambert
Question: This is multiplying a polynomial and its quite confusing for me (5-4n+4n^4)-(3+3n^4)+(8+2n^3+8n) P.S. the "^" is the exponent sign Best Answers: Can someone help me with this algebra 2 question? Isaiah | 5 days ago
Well, there are no products or parenthetical exponents to worry about, so go ahead and get rid of the parentheses. Remember that when you are subtracting a term within parentheses, you are subtracting the whole thing, so change the sign of everything within. It would become 5-4n+4n^4-3-3n^4+8+2n^3+8n. Isolate like terms. 5-3+8+8n-4n+4n^4-3n^4+2n^3. Then combine. 10+4n+n^4+2n^3. Your teacher will probably want you to put it in greatest to least form, so put it like this, n^4+2n^3+4n+10.
👍 198 | 👎 5
Did you like the answer? Can someone help me with this algebra 2 question? Share with your friends

We found more questions related to the topic: Parenthesis signs Originally Answered: Algebra 1-2 Question?
✐Explanation✐ y = mx + b m is the slope b is the y-intercept. Determine the slope first, using m = (y - y1)/(x - x1). Then, substitute the slope and the point to solve for b. Then, rewrite the new equation. Originally Answered: Algebra 1-2 Question?
You could find the slope, then plug the slope, an X value, and a Y value into the Point-Slope formula like this: Let's pretend the points are (2,4) and (4,5) The slope is (5-4)/(4-2) which equals 1/2 The Point-Slope formula is Y2-Y1=m(X2-X1), so just plug in some values: Y2-4=(1/2)(X2-2) So your equation in Point-Slope form would be: Y2-4=(1/2)(X2-2) Hope that helps... Originally Answered: Algebra question?
You need to give a specific x value to find the value of the function. Perhaps you are looking for the zeroes of the function, i.e., the value of x when the function = 0. Or maybe you're supposed to factor 3x²+4x-2. In either case, use the quadratic formula to solve    ax²+bx+c=0 where    a=3    b=4    c=-2 x = [-b ± √(b²-4ac)] / (2a)    = [-(4) ± √((4)² - 4(3)(-2))] / 2(3)    = [-4 ± √(40)] / 6    = [-4 ± √(2³)√(5)] / 6    = [-4 ± 2√(2)√(5)] / 6    = [-4 ± 2√10] / 6    = -0.667 ± 1.054 x₊ = -0.667 + 1.054 = 0.387 x₋ = -0.667 - 1.054 = -1.721 f(x) = 3x²+4x-2 = (x-0.387)(x+1.721)

If you have your own answer to the question parenthesis signs, then you can write your own version, using the form below for an extended answer.